Translation exercise: theoretical coordinates for a Latin American Marxism - Del Valle, Alejandro (2023)
This paper reviews the main points of the translation concept. Based on Martín Cortés’s study of José Aricó’s “theoretical practice”, thework explores the conceptual axes of translation, the historical and conceptual frameworks of its creation and the main problems it addresses and/or faces. The translation exercise is presented as a theoretical-practical activity of conjunctural intervention necessary for the production of a fruitful Marxism in a Latin American key